Response of Spirulina platensis C1 to High Temperature and High Light Intensity - Chaiklahan, Ratana; Khonsarn, Nittaya; Chirasuwan, Nattayaporn; Ruengjitchatchawalya, Marasri; Bunnag, Boosya; Tanticharoen, Morakot (Agriculture and Natural Resources, 2007)
Response of Spirulina platensis strain C1 to high temperature and high light intensity was studied. Specific growth rate of the S. platensis C1 cells grown in batch cultures at 35°C with a light intensity of 100 μE/m2/s was 0.0247 h-1. The specific growth rate decreased to 0.008 h-1 at 43°C, which was designated to be the critical temperature for this alga strain C1. A suddenly increasing in light intensity from 100 to 500 μE/m2/s showed an impact to the cell growth, which it had significant affects to photosynthesis (as O2-evolution) as well as its pigment content (chlorophyll and phycocyanin). However, a less effect on the alga growth was obtained when the cells were shifted to grow at higher temperature of 43°C. The alga cells grown at high temperature with high light intensity resulted in decreasing protein content while carbohydrate content increased. The fatty acid profiles of the cells grown at high temperature exhibited a decrease in polyunsaturated fatty acid (C18:3Δ6,9,12) while C18:2Δ9,12 increased. In contrast, the alga cells grown in a high light intensity showed an increase in C18:2Δ9,12, while C18:1Δ9 and total fatty acid content (TFA) were decreased. On the other hand, the combined effects of temperature and light intensity (43°C, 500 μE/m2/s) showed that the period of recovery in photosynthesis depends upon the period of exposure to the stress parameter.